Worker Wage Priority in Indonesian Corporate Bankruptcy Proceedings: Prioritas Upah Pekerja dalam Kepailitan Perusahaan di Indonesia - Rinoa Najwa Aurora Nindha Senduk; Ariawan Gunadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Employment rights require strong legal protection when business failure disrupts livelihoods and statutory entitlements. Specific Background In company insolvency, employees often face unpaid salaries, severance pay, and other employment-related claims while asset distribution is managed through bankruptcy proceedings. Knowledge Gap Although national regulations place employees as preferred creditors and Constitutional Court Decision Number 67/PUU-XI/2013 strengthens salary payment priority, implementation still faces unresolved practical barriers. Aims This study analyzes legal protection for employees in company insolvency and examines obstacles affecting the fulfillment of employment rights. Results The findings show that protection is normatively regulated through constitutional provisions, manpower law, job creation law, and bankruptcy law. Employees are recognized as preferred creditors whose salaries and related entitlements should receive priority. However, implementation is constrained by conflicts between labor and bankruptcy norms, insufficient bankruptcy assets, lengthy proceedings, weak trustee supervision, and limited employee understanding of legal rights. Novelty This study highlights the gap between normative creditor preference and actual rights fulfillment in insolvency practice. Implications Regulatory harmonization, stronger supervision, and clearer legal certainty are required to ensure fair payment of employment entitlements. Highlights: Employees are legally positioned above ordinary claimants. Asset shortages and long proceedings delay entitlement fulfillment. Harmonized rules and stronger trustee monitoring are necessary. Keywords: Legal Protection, Workers, Corporate Bankruptcy.